Optic nerve sheath fenestration for visual rehabilitation in moyamoya disease - Barh, Atanu (Saudi J Ophthalmol, 2021)
A 13-year-old female presented with decrease in vision in both eyes with headache and vomiting for 15 days. Her visual acuity was perception of light with inaccurate projection in the right eye and counting fingers close to face in the left eye. Pupils were nonreactive. Fundus showed bilateral disc edema. Magnetic resonance angiography showed an attenuated caliber of the left internal carotid artery with occlusion of the left middle cerebral artery with collaterals, characteristic of moyamoya disease. The patient underwent right optic nerve sheath fenestration, following which her vision improved to 6/36 in the right and 6/24 in the left eye. Moyamoya disease is an occlusive disease of the cerebral vasculature most commonly seen in the Japanese. Children usually present with ischemic events. In the literature, visual symptoms secondary to raised intracranial tension in moyamoya disease are not well described. Ophthalmologists should be aware of this disease and the treatment options for salvaging vision.